"Effect of Karvir Taila in the management of Garbhini Kikwis: A single case study.": Array - Pore, Shailaja (Ayurline: International Journal of Research in Indian Medicine, 2019)
Now a days as everybody is conscious about skin, its tone & complexion. Every female wants to become pregnant. During pregnancy woman has to face many physiological & anatomical changes that includes skin changes over the face & abdomen. During pregnancy each has to suffer with kikwis i.e. striae gravidarum. As it causes permanent discolouration and harmless the beauty there is need for treatment. Ayurved Acharyas have elaborated the treatment for Garbhini kikwis. In Garbhini kikwis mainly symptoms of kandu & vaivarnya. Karvir taila has mainly kapha-vata Shamak, Vranashodhan, Vranaropan & twachya